ÁP DỤNG PHÉP BIẾN ĐỔI WAVELET 2-D ĐỂ TÁCH TRƯỜNG DỊ THƯỜNG TỪ - Liệt, Đặng Văn; Cường, Đỗ Đức; Đẩu, Dương Hiếu (Tạp chí Khoa học Đại học Cần Thơ, 2004)
ABSTRACT A measurement magnetic field may be composed by regional anomalies - corresponding to low frequencies - and by local anomalies - corresponding to high frequencies. The initial step of the magnetic interpretation was the separation of local or regional anomalies from the measurement magnetic field. The Wavelet transform can be used to decompose a signal into approximation components - corresponding to high scales or low frequencies - and detail components - corresponding to low scales or high frequencies. In this manner, the Wavelet transform can be used to separate the local and regional magnetic anomalies. In this paper we used the Wavelet transform to separate the local - regional magnetic anomalies in one area's offshore ofSouth Viet Nam. The results were compared with the ones calculated by a traditional method. Keywords: Wavelet transform, multi-resotution analysis, regional anomalies, local anomalies. Title: Application of the wavelet transform 2-D to separate the magnetic anomalies.